Changes in Blood Glucose and Electrolytes (Na-K-CL) During Transurethral Resection of the Prostate Using Dextrose 5% Solution as Irrigation Fluid (Latakia University Journal -Medical Sciences Series, 2025)
Background: As it has been shown in many studies, the rareness of changes in sreum glucose and electrolytes by using dextrose 5% solution during TURP leads to considering  it as a good option for using due to its effectiveness, low pric, and lack of significant effects causes by other solutions. Thus we can adopt it as basic solution during TURP.Objectives: the main objective: Studying the level of serum  glucose and electrolytes and its effect on TURP.Evaluation of the chemical Analysis results before and after surgery.               Secondary objective: Studying the correlation of patient's clinical condition with the results of chemical analysisMaterials and methods: Statistical Study ( cross-sectional) The research sample included 100 patients with benign prostatic hyperplasia who attended the Urological Surgery Clinic at Tishreen University Hospital in Lattakia during the period between 2023-2024 and met the inclusion criterions in the research.The diagnosis of BPH was made clinically .Serum glucose was measured in the central laboratory at Tishreen University Hospital using a semi – automatic HUMAN device, using the colorimetric test method and electrolytes was measured using Urit 910 plus deviceResults: Patients' ages ranged from 49 to 82 years, with a mean of 63.93±7.2 years. The mean volume of the prostate before surgery was 56.27±4.9 gram, the mean number of irrigation units used was 14.74±3.2 liter, the mean duration of surgery was 58.80±7.9 minute. The mean level of glucose before surgery was 103.34±24.56 mg/dL. One hour after the end of surgery, it increased and reached 120.45±40.4 mg/dL, and after two hours it decreased again and reached 104.21±30.8 mg/dL with p-value=0.0001 The mean level of sodium before surgery was 139.22±3.5 mmol/L. One hour after the end of surgery it decreased and reached 137.94±3.9 mmol/L, after two hours it returned to the rise ​​and the mean was 138.65±3.6 mmol/L with p-value = 0.01. The mean level of potassium before surgery was 4.12±0.3 mmol/L. One hour after the end of surgery, it increased slightly and reached 4.23±0.4 mmol/L, and after two hours it decreased slightly and reached 4.16±0.3 mmol/L, with p-value=0.03. The mean chloride level before surgery was 100.51±2.18 mmol/L. One hour after the end of surgery, it increased slightly and reached 102.00±2.19 mmol/L, and after two hours it decreased slightly and reached 101.18±2.0 mmol/L, with p-value=0.04. None of our patients had TUR Syndrome.The mean values of ​​ glucose were high in the presence of diabetes and high blood pressure, with statistically significant differences at each follow-up time point with p-value
Keywords: TURP